A case of abscess after BCG vaccine in an immunocompetent child without other clinical signs. Issue 6 (13th December 2015) - d'Aleo, Francesco; Bonanno, Roberta; Costantino, Antonella Lo Presti; Arena, Salvatore; Midiri, Angelina; Mancuso, Giuseppe; Biondo, Carmelo; Beninati, Concetta
Abstract : Introduction: Bacille Calmette–Guérin (BCG), an attenuated strain of Mycobacterium bovis, is a rare cause of infection, with few published cases in immunocompetent individuals. Case presentation: We present the case of a cutaneous abscess in an immunocompetent infant returning from Morocco, where he received a BCG vaccination. The abscess developed at the site of inoculation in the forearm (a non-recommended site) in the absence of lymphadenopathy or systemic signs. The lesion did not recur after aspiration of the abscess and further treatment was not required. Conclusion: Infections caused by M. bovis BCG may be difficult to diagnose without systemic signs or lymphadenopathy but should be suspected in children returning from regions where BCG vaccination is widely applied. The present report suggests that abscess formation after BCG vaccination is a continuing problem, particularly in tuberculosis-endemic areas and when recommendations concerning dosage or injection techniques are not followed. Moreover, we highlight here the importance of combining phenotypic and genotypic methods for quick identification of Mycobacterium bovis BCG in abscess drainage fluids.